Óptima ubicación y dimensionamiento de bancos de capacitores usando compensación Volt-Var en micro-redes eléctricas. - Gutiérrez Serna, Gonzalo Manuel (2018)
In this work, a mathematical model is implemented to solve optimally the location and sizing of capacitor banks in a micro-grid of electrical distribution. The proposed method is by particle swarm optimization (PSO), the solution will be obtained with dynamic programming, implementing an algorithm that will be developed entirely in MATLAB. Finding an optimal location and reactive power capacity of the capacitor banks, by means of reactive power injection in one or several established bars. The algorithm calculates the optimal solution satisfying the necessary requirements to guarantee the reliability and reliability of the system, as a case study a model of a typical micro-network of 5 bars will be used, however, the algorithm was implemented in a general way and can respond correctly before systems with multiple bars. As a final analysis, we made a comparison of the uncompensated system data and the compensated system data, highlighting an improvement in voltage profiles, minimizing line losses, minimizing total system losses, improving the power factor, decreasing the maximum voltage deviation and average voltage deviation, complying with a minimum possible cost restriction criterion.